Epidemiology of National Collegiate Athletic Association women's gymnastics injuries, 2009-2010 through 2013-2014 - Kerr, Z. Y.; Hayden, R.; Barr, M.; Klossner, D. A.; Dompier, T. P. (Journal of Athletic Training, 2015)
Context: Recent injury-surveillance data for collegiate-level women's gymnastics are limited. In addition, researchers have not captured non-time-loss injuries (ie, injuries resulting in restriction of participation <1 day).